DreamWalker: Substituting Real-World Walking Experiences with a Virtual Reality - Yang, Jackie (Junrui); Holz, Christian; Ofek, Eyal; Wilson, Andy (User Interface Software and Technology (UIST) 2019, 2019)
We explore a future in which people spend considerably more time in virtual reality, even during moments when they walk between locations in the real world. In this paper, we present DreamWalker, a VR system that enables such real world walking while users explore and stay fully immersed inside large virtual environments in a headset. Provided with a real-world destination, DreamWalker ﬁnds a similar path in a pre-authored VR environment and guides the user while real walking the virtual world. To keep the user from colliding with objects and people in the real-world, DreamWalker’s tracking system fuses GPS locations, inside-out tracking, and RGBD frames to 1) continuously and accurately position the user in the real world, 2) sense walkable paths and obstacles in real time, and 3) represent paths through a dynamically changing scene in VR to redirect the user towards the chosen destination. We demonstrate DreamWalker’s versatility by enabling users to walk three paths across the large Microsoft campus while enjoying pre-authored VR worlds, supplemented with a variety of obstacle avoidance and redirection techniques. In our evaluation, 8 participants walked across campus along a 15-minute route, experiencing a virtual Manhattan that was full of animated cars, people, and other objects.